The Relationship Between Immunization, Health Insurance, Family Support, and Health Workers with Stunting Incidence - Fauzie Rahman; Anggun Wulandari; Nur Laily; Muhammad Ali Faisal; Rizqi Rifani; Intan Yustikasari; Andini Octaviana Putri; Lia Anggraini; Muhamad Azmiyannoor; Muhammad Zainal Khadafi; Ahmad Navijay (Journal of Health and Nutrition Research, 2026)
Stunting remains a critical public health concern in Indonesia, with the Banjar Regency—specifically the Aluh-Aluh Public Health Center working area—reporting a persistently high prevalence. Beyond direct nutritional factors, stunting is influenced by underlying determinants such as access to health services and the quality of household caregiving. This study aimed to analyze the associations between immunization status, health insurance ownership, family support, and health worker support with the incidence of stunting among children under five. Methods: A quantitative case-control study was conducted involving 144 children (72 stunted cases and 72 non-stunted controls). Participants were selected through a two-stage sampling process: purposive selection of high-risk villages followed by random selection of eligible children, matched by sex. Data were collected via structured questionnaires and secondary anthropometric data from the e-PPGBM system. Statistical analysis was performed using univariate and bivariate chi-square tests to determine odds ratios (OR) and 95% confidence intervals (CI). The findings indicated no significant associations between stunting and immunization status (p = 1.000), health insurance ownership (p = 0.717), or health worker support (p = 0.074). However, family support was significantly associated with stunting incidence (p = 0.040). Children receiving poor family support had 2.385 times higher odds of being stunted compared to those receiving good support (OR = 2.385; 95% CI = 1.026–5.545). While access to health services is an important framework, household-level caregiving practices—manifested through family support—play a decisive role in stunting prevention in this setting